(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Cloud computing is a model for giving on demand internet access to common pools of configurable computer assets (e.g., networks, computers, memory, apps, and applications) that might be instantly given and released with minimum administrative effort or participation from service providers. Clouds computer has risen to prominence as a key technical trend, with several experts anticipating that it would transform IT processes and the IT sector. Users may download software, storage, and software frameworks through the Internet using a variety of devices, including PCs, notebooks, cell phones, and PDAs, thanks to cloud services supplied by clouds computer companies. This article provides an introduction of clouds computer technologies installation techniques, classifications, and characteristics. The term "cloud computing" refers to a type of computer and communications technology that provides on-demand services. There is no precise meaning for the word Cloud Computing.